Leadership In Public Sector Reforms: Navigating Transformational And Transactional Approaches Across Diverse Contexts - Ananda, Rizki; Eldita, Sirda; Aljannah, Fathimah Qotrunnada (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
Administrative reform in the public sector, a global imperative, relies heavily on the quality of leadership. This study explores the intricate dynamics between leadership styles—specifically transformational and transactional—and their impact on successful administrative reforms across varied national contexts. Through a systematic literature review of academic sources published between 2000 and 2024, sourced from databases including Taylor Francis Online, Springer Link, and Scopus, this research uncovers key trends and insights. The findings highlight the robust correlation between transformational leadership and favorable reform outcomes, though this link is moderated by contextual factors. These include entrenched organizational structures, deep-rooted cultural norms, political control over bureaucratic processes, and a nation's capacity for institutional change. Such variables can either enhance or inhibit the effectiveness of leadership, even in the most capable hands. This study underscores the need for further research to elucidate the complex interplay of leadership and reform within specific national and cultural contexts. A deeper understanding of these dynamics will equip public sector leaders to navigate the often-unpredictable landscape of administrative reforms more effectively.